Weight of backpacks and musculoskeletal pain among Iranian elementary school students - Soh, Kim Geok; Ghiami, Zeinab; Khallaghi, Karim; Soh, Kim Lam (Human Resource Management Academic Research Society, 2017)
The study aims to investigate the relationship between the weight of backpacks and musculoskeletal pain among Iranian elementary school students. In addition, this study also aims to identify the common pain areas reported among Iranian elementary school students as the result of carrying heavy backpacks. The subjects of the study consisted of 1118 females and 5474 males’ students from elementary school at all different grades. They represented 36 schools which were selected based on stratified random sampling out of all elementary schools in Quchan, Iran. Students as well as their bags and backpacks were separately weighed using a calibrated weight scale. The mean weights of students and their bags and backpacks were also calculated for each grade. Musculoskeletal questionnaire was administered to 23% of female and 9% of male students through an interview procedure to find the difference between males and females musculoskeletal pain. The results showed that the male first and third-graders carried backpacks which were respectively 9.9% and 9.0% of their body weight. While the female first and third-graders’ backpacks and second-graders’ were reported to be heavier with the backpacks weight of 10.2% and 10.4% of their body weights, respectively. It was concluded that elementary students considering their average weight, carry heavy bags to school (higher than the standard bag weight, i.e., 3-5% of body weight). In addition, the findings showed the existence of different musculoskeletal problems among female and male students. The commonest pain areas among males were neck (24.9%) and backbone (24.6%) and among females were knees (51.9%) and shoulders (34.5%).